Pengaruh Harga, Kepercayaan, Penggunaan Aplikasi dan Promosi terhadap Keputusan Pembelian di Shopee pada Masa Pandemi Covid – 19 - Arini Fauziah; Satria Tirtayasa (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
In this era, especially during the Covid-19 pandemic, people are using technology to buy and sell goods or services via the internet to reduce direct contact to prevent the spread of the Covid 19 virus. This phenomenon is known as electronic commerce or e-commerce. The e-commerce phenomenon provides a choice of ways to shop for people without the need to come directly to the store. Shopee is the most popular marketplace for online shopping, followed by Tokopedia, Bukalapak and Lazada. Shopee is the e-commerce site with the most visits in Indonesia during the pandemic, namely in Q3 with an average total visit of 96 million per month. The purpose of this study was to determine and analyze the effect of price, trust, ease of use, and promotion on online shopping decisions at Shopee during the Covid-19 pandemic. The sampling technique in this study was probability sampling so that a sample of 98 students of the Faculty of Economics and Business University of Muhammadiyah North Sumatra. Data collection techniques in this study using questionnaires and documentation. The data analysis technique used is a quantitative approach with descriptive statistical analysis, classical assumption test and hypothesis testing. The data processing in this study used SPSS 16 software. The results showed that price, trust, application use and promotion partially influenced purchasing decisions.